2016
DOI: 10.1371/journal.pone.0168284
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs as Breast Cancer Prognosis Markers through the Cancer Genome Atlas

Abstract: Breast cancer is the second-most common cancer and second-leading cause of cancer mortality in American women. The dysregulation of microRNAs (miRNAs) plays a key role in almost all cancers, including breast cancer. We comprehensively analyzed miRNA expression, global gene expression, and patient survival from the Cancer Genomes Atlas (TCGA) to identify clinically relevant miRNAs and their potential gene targets in breast tumors. In our analysis, we found that increased expression of 12 mature miRNAs—hsa-miR-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 72 publications
5
82
0
Order By: Relevance
“…High expression of miR-30a (-3p and -5p) is significantly associated with reduced RFS and better OS in our patient cohort, in agreement with 2 independent The Cancer Genome Atlas breast cancer datasets (54). Low miR-30a levels were described in aggressive breast cancer cell lines (54), breast cancer patient plasma, and tumor tissue, in association with high stage and decreased RFS and disease-free survival (55,56). The protective effects of miR-30a have been attributed to the downregulation of target genes involved in migration, invasion, apoptosis, and proliferation (57)(58)(59); regulation of epithelial-mesenchymal transition (EMT) by downmodulating vimentin (60); increasing expression of tight-junction proteins claudin 1, 2, and 3 (54); inhibition of cell self-renewal (61); and switching from glycolysis to mitochondrial respiration (62).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…High expression of miR-30a (-3p and -5p) is significantly associated with reduced RFS and better OS in our patient cohort, in agreement with 2 independent The Cancer Genome Atlas breast cancer datasets (54). Low miR-30a levels were described in aggressive breast cancer cell lines (54), breast cancer patient plasma, and tumor tissue, in association with high stage and decreased RFS and disease-free survival (55,56). The protective effects of miR-30a have been attributed to the downregulation of target genes involved in migration, invasion, apoptosis, and proliferation (57)(58)(59); regulation of epithelial-mesenchymal transition (EMT) by downmodulating vimentin (60); increasing expression of tight-junction proteins claudin 1, 2, and 3 (54); inhibition of cell self-renewal (61); and switching from glycolysis to mitochondrial respiration (62).…”
Section: Discussionsupporting
confidence: 89%
“…High expression of miR-30a (-3p and -5p) is significantly associated with reduced RFS and better OS in our patient cohort, in agreement with 2 independent The Cancer Genome Atlas breast cancer datasets (54). Low miR-30a levels were described in aggressive breast cancer cell lines (54), breast cancer patient plasma, and tumor tissue, in association with high stage and decreased RFS and disease-free survival (55,56).…”
Section: Discussionsupporting
confidence: 87%
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…-5p)[39][40][41][42][43][44][45][46] ; gastric cancer (miR-374b-5p, miR-200c-3p, miR-18b-5p, miR-196a-5p, miR-21-5p, and miR-20a-3p)[47][48][49][50][51] ; ovarian cancer (miR-141-5p, miR-182-5p, miR-483-3p, and miR-200c-3p)[52][53][54][55] ; hepatocellular carcinoma (miR-135a-5p, miR-187-3p, miR-148a-5p, miR-200a-3p, and miR-9-3p)[56][57][58][59] ; colorectal cancer…”
mentioning
confidence: 99%
“…The expression of four of the observed DE miRNAs (miR-142-5p, miR-150-5p, miR-320a, and miR-4433b-5p) selected were further validated by RT-qPCR (test phase) in a larger number of samples. These miRNAs have been previously characterized by their oncogenic and/or tumor suppressor function in other types of cancers, including BC [29,45,46], except for miR-4433-5p, that is a new miRNA with no description in cancer so far.…”
Section: Discussionmentioning
confidence: 99%